Acute Sub temporal and Infratemporal Dumbbell Abscess Secondary to Tooth Extraction: Case Report - Roka, Yam Bahadur (Eastern Green Neurosurgery, 2021)
To present a case of acute temporal and infratemporal dumbbell abscess following tooth extraction and discuss the possible anatomic pathways of spread of odontogenic infections. This is a case of right maxillary tooth extraction following which he developed local infection that spread to the temporal and sub temporal space. The history and examination revealed the infection spreading to the buccal and sub temporal space with trismus and feeding problems. Intraoral and external drainage along with antibiotics led to the resolution of the abscess. Of the many complications of tooth extraction infection spreading along the temporalis with formation of a dumbbell abscess can lead to severe discomfort and septicemia if not detected and treated early. A case with successful management and result are discussed.